PENGEMBANGAN MEDIA POP-UP BOOK BAGIAN-BAGIAN TUMBUHAN DALAM MENINGKATKAN HASIL BELAJAR IPA DI SEKOLAH DASAR - Via Amelia Firmansyah; Aan Widiyono (STKIP Subang, 2025)
This development research was conducted due to students difficulties inunderstanding the material on parts of plants during the learning process, whichled to low learning outcomes. The aim of this study was to develop a Pop-Up Bookmedia to improve the learning outcomes of sixth-grade students in science,specifically in the topic of plant parts.The research employed the Research andDevelopment (R&D) method, focusing on the development of Pop-Up Book media.The Pop-Up Book was specifically designed for sixth-grade elementary schoolstudents. The research was limited to six stages of development: (1) needsanalysis, (2) planning, (3) initial product development, (4) field testing, (5) finalproduct revision, and (6) implementation.The study involved 22 sixth-gradestudents at SDN 3 Krapyak, Jepara. Media validation was conducted by two mediaexperts and one subject matter expert. The validation results showed that MediaExpert 1 gave a feasibility score of 82%, Media Expert 2 gave 90%, and theSubject Matter Expert gave 82%, indicating that the Pop-Up Book media is highlyfeasible for use in teaching.The students’ average pre-test score was 67.35, whilethe average post-test score was 81.77. A paired sample t-test was used toexamine the effectiveness of the media, resulting in a significance value (Sig. 2-tailed) of 0.000 (<0.05). This indicates a significant difference in student learningoutcomes before and after using the Pop-Up Book media.In conclusion, the use ofthe Pop-Up Book media significantly improved students learning outcomes in thetopic of plant partsKeywords: Media pop up book, Hasil belajar, IPA.